2017
DOI: 10.1055/s-0043-101919
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Improves Insulin Sensitivity through Inhibition of STAT3/Srebp-1c-Mediated Lipid Accumulation and Inflammation in Mice fed a High-Fat Diet

Abstract: In the past few years, metabolic disorders, such as type 2 diabetes and metabolic syndrome, have reached global prevalence. Lycopene is one of the major carotenoids in tomatoes, watermelons, red grapefruits, and guava. In the current study, using high fat diet (HFD)-fed mice, we investigated the effect of Lycopene on insulin resistance. We showed that diet containing Lycopene significantly prevented HFD-induced increase of fasting blood glucose and insulin level, glucose and insulin intolerance, and decrease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 53 publications
2
27
2
Order By: Relevance
“…The treatment with lycopene for 35 days avoided the progressive increase in the postprandial glycemia, which could be a consequence, at least in part, of the improvements observed in the glucose tolerance. Supporting this hypothesis, studies have found that supplementations with lycopene 34 or with dry tomato peel 35 reduced both the glucose intolerance and the insulin resistance in high-fat diet-fed mice. In addition, a recent review by Zhu et al 36 supports evidence of the lycopene beneficial effects on maintaining the pancreatic function in in vivo models of metabolic dysfunctions.…”
Section: Discussionmentioning
confidence: 95%
“…The treatment with lycopene for 35 days avoided the progressive increase in the postprandial glycemia, which could be a consequence, at least in part, of the improvements observed in the glucose tolerance. Supporting this hypothesis, studies have found that supplementations with lycopene 34 or with dry tomato peel 35 reduced both the glucose intolerance and the insulin resistance in high-fat diet-fed mice. In addition, a recent review by Zhu et al 36 supports evidence of the lycopene beneficial effects on maintaining the pancreatic function in in vivo models of metabolic dysfunctions.…”
Section: Discussionmentioning
confidence: 95%
“…Based on the potent antioxidant and lipid-lowering properties of lycopene, different studies have assessed it as a beneficial nutrient for the prevention and treatment of MetS. Animal and human-based studies have shown that lycopene reduces blood pressure [ 210 , 211 ], atherosclerotic burden [ 248 ] and improves blood antioxidant capacity [ 246 , 249 ], has an anti-obesity role [ 212 , 213 ], improves insulin sensitivity, reduces hyperglycemia [ 216 , 217 ], and improves the lipid profile [ 214 , 215 ]. Moreover, a retrospective study with 2500 patients with MetS showed that higher serum levels of lycopene are associated with a reduced risk of death [ 250 ].…”
Section: Nutrients (Well-being Through Feeding)mentioning
confidence: 99%
“…These findings suggest MCA prevented increases in the level of glucose in plasma, and improved insulin sensitivity. Lycopene has been showed to have significant inhibitory effects on HFD-induced insulin resistance by preventing the expression and phosphorylation of STAT3 in a mouse model [36]. In addition, plasma ß-carotene has been shown to have reversed correlation with insulin resistance [37].…”
Section: Discussionmentioning
confidence: 99%